Didactic proposal to develop critical cosmopolitan competences and skills in historical thinking from the situation-problem methodology - García Leiva, Ernesto (Universidad Nacional del Litoral, 2020)
This essay reflects on the meaning of the discipline of History in the postmodern world and on its pedagogical possibilities in the educational environment, so that throughout this article we investigate the renewal of teaching activity within the subject of History. For this we design a didactic proposal that is based on critical teaching and participatory learning, so we implement the situation-problem methodology. This proposal aims to promote hermeneutical skills in the analysis of sources and representations to know the events of the past. In relationship with it we develop historical thinking and critical cosmopolitan competences in students. We practice our didactic proposal in a course of 4 ESO, within the Spanish education system, to later work out the results.